2023
DOI: 10.1177/00031348231160833
|View full text |Cite
|
Sign up to set email alerts
|

The Intersection of Race and Rurality and its Effect on Colorectal Cancer Survival

Abstract: Introduction Outcomes in colorectal cancer treatment are historically worse in Black people and residents of rural areas. Purported reasons include factors such as systemic racism, poverty, lack of access to care, and social determinants of health. We sought to determine whether outcomes worsened when race and rural residence intersected. Methods The National Cancer Database was queried for individuals with stage II–III colorectal cancer (2004-2018). To examine the intersectionality of race/rurality on outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 18 publications
1
0
0
Order By: Relevance
“…Previous research at our institution examining 5-year survival outcomes in patients with CRC suggested that race and rurality may act synergistically to worsen outcomes. 20 Similar analysis in this study, using Race/ Ethnicity as a common variable, demonstrated expected findings in the Metro groups with the Metro-non-Hispanic White group having shorter time to surgery than either the Metro-non-Hispanic Black or the Metro Hispanic groups. However, the expected findings of longest wait times in the rural minority groups were not demonstrated in our analysis.…”
Section: Discussionsupporting
confidence: 80%
“…Previous research at our institution examining 5-year survival outcomes in patients with CRC suggested that race and rurality may act synergistically to worsen outcomes. 20 Similar analysis in this study, using Race/ Ethnicity as a common variable, demonstrated expected findings in the Metro groups with the Metro-non-Hispanic White group having shorter time to surgery than either the Metro-non-Hispanic Black or the Metro Hispanic groups. However, the expected findings of longest wait times in the rural minority groups were not demonstrated in our analysis.…”
Section: Discussionsupporting
confidence: 80%